THE IMPORTANCE OF MOTORIC FACTORS ON REALIZATION OF ELEMENTS OF ACROBATICS IN RELATION TO THE RESPONDENTS' STATURE - Jovica Petković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
The research has been done with an aim to set down the difference related to mo- toric abilities and successful realization of the competitive gymnastics curriculum (for- ward roll and backward roll) depending on the respondents' growth. This work is based on the sample of 51 fifth grade primary school children and 50 students of the fourth grade from the secondary school, all coming from the municipality of Niksic. All respondents were tested with ten mobility tests and two specific mobility tasks which were adjusted to the mentioned growth